A Hybrid Model for Teaching Settlement Skills - Debra Berman; Catherine Greene Burnett (Washington University Journal of Law and Policy, 2023)
For decades, legal educators have grappled with ensuring that law school curriculum continues to fulfill its foundational role in a student’s life- long legal education while adjusting to evolving learning expectations and needs. Educators weigh several educational goals when developing curriculum and focus on three major learning categories: doctrinal knowledge, skills and competencies, and values and professionalism. This Article addresses the tension between authentic experience and ensuring skills development in creating Alternative Dispute Resolution (ADR) curriculum for law students. ADR classes provide educators an opportunity to emphasize the development of specific skillsets through controlled simulated environments whereas clinics or competitions may offer more “real-world” experiences at the cost of a professor’s ability to foster skills development. This Article advocates for a hybrid approach to ADR curriculum which combines traditional simulation experiences with traditional clinical experiences. The Authors are not advocating for the elimination of traditional in-class simulations but instead propose that their proposed system can serve as an enhancement to simulated experiences. The Authors argue that a hybrid approach will fill the holes in ADR curriculum by providing meaningful opportunities for real-world settlement practice that simulation classes frequently lack while fostering skills development in ways clinics and competitions typically do not.
Keywords: legal education; negotiation; settlement; ADR; alternative dispute resolution; clinics; curriculum; education; educators; classroom